2011
DOI: 10.3354/meps09218
|View full text |Cite
|
Sign up to set email alerts
|

Predation constrains host choice for a marine mesograzer

Abstract: For small sedentary herbivores that inhabit seaweeds, choosing a host that provides adequate nutrition and refuge should be favored by natural selection. Yet, the relative importance of seaweed nutritional value versus habitat quality in driving mesograzer host choice remains poorly understood for most herbivores. Previous work in coastal North Carolina, USA, and 2 tropical locations suggests that amphipods often utilize host seaweeds that offer superior refuge from both omnivorous and carnivorous consumers. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…Unpublished data shows that gammarid amphipods tethered in the field in Bodega Bay without access to preferred microhabitat are rapidly consumed (50-100% consumed within 24 h; J. Stachowicz unpubl.). This is consistent with data for other epifauna from similar systems, which can shift their microhabitat use in the presence of predators to a substrate with higher value as shelter (Zamzow et al 2010, Beermann andBoos 2015), or suffer increased mortality from predation in the absence of their preferred host plant (Holmlund et al 1990, Duffy and Hay 1991, Moran et al 2010, Lasley-Rasher et al 2011. However, we found that the presence of two fish predators did not influence mesograzers in their microhabitat use even though the predators were very active and attempted to feed on the grazers behind the mesh barrier.…”
Section: Effects Of Instantaneous Versus Sustained Predation Pressuresupporting
confidence: 90%
See 2 more Smart Citations
“…Unpublished data shows that gammarid amphipods tethered in the field in Bodega Bay without access to preferred microhabitat are rapidly consumed (50-100% consumed within 24 h; J. Stachowicz unpubl.). This is consistent with data for other epifauna from similar systems, which can shift their microhabitat use in the presence of predators to a substrate with higher value as shelter (Zamzow et al 2010, Beermann andBoos 2015), or suffer increased mortality from predation in the absence of their preferred host plant (Holmlund et al 1990, Duffy and Hay 1991, Moran et al 2010, Lasley-Rasher et al 2011. However, we found that the presence of two fish predators did not influence mesograzers in their microhabitat use even though the predators were very active and attempted to feed on the grazers behind the mesh barrier.…”
Section: Effects Of Instantaneous Versus Sustained Predation Pressuresupporting
confidence: 90%
“…One of the reasons that microhabitat choice is thought to be important in plant–arthropod systems such as this one has to do with the need for ‘enemy‐free‐space’ (Duffy and Hay , Berdegue et al ). In particular, if predation susceptibility is determined by the match between grazer and plant morphology, using a microhabitat that poses a less optimal fit might result in increased exposure to predators (Duffy and Hay , Boström and Mattila , Lasley‐Rasher et al ). Unpublished data shows that gammarid amphipods tethered in the field in Bodega Bay without access to preferred microhabitat are rapidly consumed (50–100% consumed within 24 h; J. Stachowicz unpubl.).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meso-invertebrates inhabiting the host species exhibit tradeoffs in their host plant choice between nutritional value of the seaweed, the value of the seaweed as a shelter from intense predation, and the availability of palatable seaweed in the environment (Duffy & Hay 1991;Lasley-Rasher et al 2011). They are important members of seaweed assemblages as they can affect ecological processes such as recruitment potential, biofouling, and fish behaviour (Enge, Nylund & Pavia 2013; Wright et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A habitat architecture that provides hiding from predators is crucial (Zamzow et al, 2010) and often valued more than food (Norderhaug, 2004) by marine amphipods. Indeed, amphipods were more abundant on marine macroalgae providing refuge from predation than on vegetation they preferentially fed on, both in laboratory and in situ (Duffy & Hay, 1991;Lasley-Rasher et al, 2011).…”
Section: Refuge: Light Avoidance and Habitat Architecturementioning
confidence: 98%